Das Experteninterview als Datenerhebungsmethode in Prüfungsarbeiten - Frank Wernitz (IUBH Internationale Hochschule, 2018)
– This paper examines the key elements of the expert interview as a method of data generation. First, its characteristics are settled in order to classify this specific type of interview within the range of interview - techniques in general. Furthermore, some of the most important sources of error in application of the method are discussed including interviewer - and context - based problems. Then the characteristics of a "good" interviewer are specified. The main focus lies on the process flow of an expert interview including the different phases from prearrangement to data evaluation and especially the creation of an interview guideline. Finally, some possible extensions and directions of future research are discussed.
urn:nbn:de:101:1-2018102211510147349744
Keywords: A22; B41; C81; 650; Methodik; qualitative Forschung; Interview; Befragung; Datenerhebung; Datenauswertung; Experten